PENGEMBANGAN E-BOOKLET BERBASIS LITERASI SAINS PADA MATERI SISTEM REPRODUKSI UNTUK PEMBELAJARAN BIOLOGI DI SMA - Rismawati, Wheny; Sri Wulandari; Darmadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to produce a Science Literacy-Based E-Booklet on the human reproductive system topic for grade XI high school students that is suitable for use as a biology learning medium. The research was conducted at the Biology Education Study Program, Faculty of Teacher Training and Education, University of Riau, from September 2024 to March 2025. This study is a Research and Development (R&D) type using the ADDIE model, which was carried out up to the development stage, as the focus is on developing a digital learning material to assist teachers in the learning process and to improve students’ understanding of biological concepts. The research instruments consisted of interview sheets, validation sheets, and response questionnaires using a Likert scale of 1–5. The data were analyzed descriptively to assess validation results, user responses, and the quality of the developed E-Booklet. The results showed that the media validation obtained a score of 87,33% in the very valid category, material validation 80,00% in the very valid category, first trial 89,59%, and second trial 81,00% in the very good category. The overall average score of 85,09% indicates that the Science Literacy-Based E-Booklet on the human reproductive system has a very good quality and is feasible to be implemented in biology learning for grade XI high school students.